Metastasis Model of Cancer Stem Cell-Derived Tumors - Hager Mansour; Ghmkin Hassan; Said M. Afify; Ting Yan; Akimasa Seno; Masaharu Seno (Methods and Protocols, 2020)
Metastasis includes the dissemination of cancer cells from a malignant tumor and seed in distant sites inside the body forming secondary tumors. Metastatic cells from the primary tumor can move even before the cancer is detected. Therefore, metastases are responsible for more than 90% of cancer-related deaths. Over recent decades there has been adequate evidence suggesting the existence of CSCs with self-renewing and drug-resistant potency within heterogeneous tumors. Cancer stem cells (CSCs) act as a tumor initiating cells and have roles in tumor retrieve and metastasis. Our group recently developed a unique CSC model from mouse induced pluripotent stem cells cultured in the presence of cancer cell-conditioned medium that mimics tumors microenvironment. Using this model, we demonstrated a new method for studying metastasis by intraperitoneal transplantation of tumors and investigate the metastasis ability of cells from these segments. First of all, CSCs were injected subcutaneously in nude mice. The developed malignant tumors were minimized then transplanted into the peritoneal cavity. Following this, the developed tumor in addition to lung, pancreas and liver were then excised and analyzed. Our method showed the metastatic potential of CSCs with the ability of disseminated and moving to blood circulation and seeding in distant organs such as lung and pancreas. This method could provide a good model to study the mechanisms of metastasis according to CSC theory.